Investigating the Integration of Nonwoven Carbon Fibers for Mechanical Enhancement in Compression Molded Fiber-Reinforced Polymer Bipolar Plates - Frank, Rainer; Wittmann, Lisa-Maria; Kleffel, Tobias; Roth, Benedikt; Graichen, Knut; Drummer, Dietmar (Polymers, 2023)
The demand for polymer composite solutions in bipolar plates for polymer electrolyte membrane fuel cells (PEMFCs) has risen due to advantages over metal plates such as longer lifetime, weight reduction, corrosion resistance, flexible manufacturing, freedom of design, and cost-effectiveness. The challenge with polymer composites is achieving both sufficient electrical conductivity and mechanical stability with high filler content. A carbon fiber fleece as reinforcement in a graphite-filled polypropylene (PP) matrix was investigated for use as bipolar plate material with increased mechanical and sufficient conductive properties. Plates with a thickness of 1 mm containing four layers of fleece impregnated in the PP-graphite compound were produced in a compression molding process. Particle and fiber interactions were investigated via microscopy. The plates were characterized with respect to the electrical conductivity and mechanical stability. High electric conductivity was reached for fiber-reinforced and plain PP-graphite compound plates, with increased filler content leading to a higher conductivity. The contact resistance remained largely unaffected by surface etching as no polymeric skin layer formed during compression molding. Fiber-reinforced plates exhibit twice the tensile strength, a significantly higher tensile modulus, and an increased elongation at break, compared to PP filled only with graphite.
CRIS-Team Scopus Importer:2023-10-20
Keywords: bipolar plate; carbon fleece; compression molding; fiber reinforcement; fuel cell